الصكوك الاستثمارية الإسلامية بين ماليزيا ومصر: دراسة فقهية مقارنة = Islamic investment Sukuk between Malaysia and Egypt: a juristic comparative study - Tawfeeq, Abu Baker; Ibrahim Mohamed, Hossam El Din (Department of Fiqh and Usul Fiqh, Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
In this research, the researchers attempt to illustrate the linguistic and terminological meanings of Sukuk. They also want to point out their importance in financing major projects. Additionally, they try to recall the role of Islamic Sukuk in the contemporary world. This role will be shown by comparing between Sukuk in Malaysia and Egypt. This research will determine the historical stages through which the project of Sukuk in the Arab Republic of Egypt has passed. It will also explain Al-Azhar's response to the Sukuk project in the past, and show that currently, Islamic Sukuk is the only ideal mechanism for large projects in Egypt. A study will be conducted on the full text of the remarks made by the Supreme Council of Scholars in Al-Azhar on the Islamic Sukuk law. As for the research methodology, the researchers will follow two basic methods in this study: first, the inductive method to extract the related information from the sources; second, analytical method to analyze those information and compare between the two countries Malaysia and Egypt.